Patient Transfer to Receive Proton Beam Therapy During Intensive Multimodal Therapy is Safe and Feasible for Patients With Newly Diagnosed High-risk Neuroblastoma. Issue 1 (January 2020) - Hosaka, Sho; Fukushima, Hiroko; Nakao, Tomohei; Suzuki, Ryoko; Yamaki, Yuni; Tanaka, Keiichi; Saito, Takashi; Mizumoto, Masashi; Sakurai, Hideyuki; Fukushima, Takashi; Takada, Hidetoshi
Abstract : Neuroblastoma (NB) predominantly presents as high-risk disease, requiring intensive multimodal therapy. Proton beam therpy (PBT) is a promising option for many childhood cancers, but is not widely available. Patients with NB hoping to receive PBT may therefore need to be transferred between institutions during intensive multimodal therapy, risking undesirable effects. We evaluated patients with high-risk NB who received PBT at our institute as part of first-line therapy, mainly focusing on the safety and feasibility of mid-treatment patient transfer. Eighteen patients with newly diagnosed high-risk NB who received PBT between April 2010 and June 2016 were retrospectively analyzed for local control, outcomes, and toxicity. Survival (3-y overall survival 71%±11%; 3-y event-free survival 44%±12%) and local control rate (100%) were comparable with previous studies. Few acute adverse events were recorded, and all patients completed PBT without treatment delay. PBT for high-risk NB was safe and feasible for patients requiring mid-treatment interinstitutional transfer.